Consolidation chemotherapy prior to hematopoietic cell transplantation for adults with acute myeloid leukemia in first remission. Issue 4 (December 2016) - Appelbaum, Frederick R.
Abstract: Whether patients with acute myeloid leukemia (AML) should receive routine consolidation chemotherapy prior to transplant remains a significant question. Consolidation therapy may be advisable in the face of transplant delays, such as donor identification, insurance clearance, or transplant center scheduling, to prevent relapse prior to transplant. However, in cases where physicians have a choice, the question of the value of consolidation chemotherapy continues to be debated. This paper reviews the value of consolidation therapy in 4 different transplant settings.